2012
DOI: 10.1186/bcr3111
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin (GP88) tumor tissue expression is associated with increased risk of recurrence in breast cancer patients diagnosed with estrogen receptor positive invasive ductal carcinoma

Abstract: IntroductionGP88 (progranulin) has been implicated in tumorigenesis and resistance to anti-estrogen therapies for estrogen receptor positive (ER+) breast cancer. Previous pathological studies showed that GP88 is expressed in invasive ductal carcinoma (IDC), but not in normal mammary epithelial tissue, benign lesions or lobular carcinoma. Based on these results, the present study examines GP88 prognostic significance in association with recurrence and death risks for ER+ IDC patients.MethodsTwo retrospective mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 30 publications
4
48
0
1
Order By: Relevance
“…This study revealed that preoperative serum PGRN levels are clinically significant for predicting recurrence in patients with hormone receptor-positive tumors; however, these data have several limitations that are important to consider when interpreting the study’s results [80]. Serrero et al [81] also analyzed PGRN expression by immunohistochemistry in paraffin-embedded breast tumor sections from patients with estrogen receptor-positive invasive ductal carcinoma. Their results showed that high PGRN expression was associated with a decrease in disease-free and overall survival as well as a 5.9-fold higher hazard of disease recurrence and a 2.5-higher mortality risk compared to patients with low PGRN expression in the tumor tissue.…”
Section: Progranulin As Cancer Biomarkermentioning
confidence: 99%
“…This study revealed that preoperative serum PGRN levels are clinically significant for predicting recurrence in patients with hormone receptor-positive tumors; however, these data have several limitations that are important to consider when interpreting the study’s results [80]. Serrero et al [81] also analyzed PGRN expression by immunohistochemistry in paraffin-embedded breast tumor sections from patients with estrogen receptor-positive invasive ductal carcinoma. Their results showed that high PGRN expression was associated with a decrease in disease-free and overall survival as well as a 5.9-fold higher hazard of disease recurrence and a 2.5-higher mortality risk compared to patients with low PGRN expression in the tumor tissue.…”
Section: Progranulin As Cancer Biomarkermentioning
confidence: 99%
“…Progranulin has been reported to activate many of the typical cell proliferation signaling pathways, including ERK, PI3K, and Akt pathways (48,50,51), not only in tumor cells but also in neurons (52,53). Progranulin may be a prognostic marker (54) or a therapeutic target in cancer: progranulin overexpression confers an aggressive phenotype to adenocarcinoma (46), immortalized ovarian epithelial cells (55), breast cancer (49,56), and hepatocellular carcinoma (57), and anti-progranulin treatment reduces in vivo tumorigenicity of teratoma (58) and breast cancer cell lines (59). However, it should be emphasized that although these early studies strongly linked progranulin to cancer, no cell surface receptor has been shown to mediate these effects.…”
Section: What Does Progranulin Do?mentioning
confidence: 99%
“…Analysis of GP88 tissue expression in 600 cases of estrogen receptor positive, invasive ductal carcinoma in relation with clinical outcomes demonstrated that high GP88 expression was statistically associated with a 5.9-fold higher hazard of disease recurrence (p< 0.0001) and a 2.5-fold higher mortality hazard (p=0.0002) compared to patients with no or low expression of tumor GP88 (14). GP88 remained an independent risk predictor after considering age, ethnicity, nodal status, tumor size, tumor grade, disease stage, progesterone receptor expression and treatments (14).…”
Section: Introductionmentioning
confidence: 99%
“…GP88 remained an independent risk predictor after considering age, ethnicity, nodal status, tumor size, tumor grade, disease stage, progesterone receptor expression and treatments (14). Since GP88 is a secreted protein, a prospective longitudinal clinical study to measure circulating level of GP88 with an Enzyme Immunoassay (EIA) developed in our laboratory demonstrated the performance of the serum GP88 EIA by establishing a basal range for GP88 in serum from healthy volunteers of 28 ng/ml and showing that serum GP88 levels in breast cancer patients was elevated to 40 ng/ml in early stage and over 100 ng/ml in later stages of breast cancer (15).…”
Section: Introductionmentioning
confidence: 99%